Politik Lokal Dalam Pengelolaan Keamanan Dan Kebersihan Lingkungan Studi Pada Kelurahan Sungaiselincah Kecamatan Kalidoni Kota Palembang Tahun 2025 - Mulyadi Mulyadi; Ryllian Chandra Eka Viana; Deany Afriany (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This research aims to understand and analyze how local politics plays a role in managing environmental security and cleanliness in Kelurahan Sungaiselincah, Kecamatan Kalidoni, Kota Palembang. Local politics is an important instrument in regional development because it determines policy direction, inter-agency coordination, and community participation in maintaining environmental order and cleanliness. In practice, the management of security and cleanliness in Kelurahan Sungaiselincah still faces various challenges, ranging from high crime rates, lack of street lighting, lack of community participation, to suboptimal waste management. This research uses a qualitative approach with a case study method. Data collection techniques included in-depth interviews with village officials, RT/RW heads, and local communities; direct observation at the location; and documentation from various primary and secondary sources. Data analysis was conducted descriptively-qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results show that local politics plays an important role in shaping security policies and coordination through the Siskamling program and cooperation with the police. In terms of cleanliness, the kelurahan government initiated community service programs, environmental awareness campaigns, and procurement of trash bin facilities. However, the effectiveness of these policies is hampered by low community awareness, budget constraints, and weak synergies between local actors. This research emphasizes the importance of implementing collaborative governance that involves all stakeholders to create a safe, clean and sustainable environment.